Types of Epidendrum antenniferum Bonpl. and Its Synonyms (Orchidaceae, Oncidiidae) - Navarro-Romo W.C. (2020)
The names Epidendrum antenniferum Bonpl. and Trichoceros muscifera Kraenzl. (Orchidaceae, Oncidiidae) are lectotypified using digital images from the original material preserved at P and HBG, respectively. The holotype of Trichoceros parviflorus Kunth is kept at P and that of T. armillatus Rchb. f. at G. © Finnish Zoological and Botanical Publishing Board.